The Preliminary Study of Organizational Culture, Organizational Capabilities and Communication to Improve Human Resources Development Performances in Saudi Arabia: Strategic Fit with Higher Educations as Moderating Variable - Hassan Al Nasser, Ali; Jais, Juraifa (International Journal of Psychosocial Rehabilitation, 2020)
Higher education is crucial for the development of any country economically, politically, and socially. Economically, higher education could be integrated into business towards solving the contemporary Human Resource Development. Even thoughmost of the countries in the Middle East (Saudi Arabia inclusive) are rich in oil and other natural resources, yet the regions are classified under the resource-rich, labour importing category as they do not have a sufficient labour force to meet the demand for skilled labour. The Saudi government has made numerous attempts in enabling individual employability and national economic growth through scholarships offering. However, whether the incentives and interventions made by the Saudi government adequate or not has yet been determined. Hence, the current study begins by looking at human resource development challenges in Saudi Arabia, mainly focusing on the contribution of Saudi’s higher education to the national development of human resources and the plans that are available to develop the needed human resource. The study seeks to provide a strategic fit as a moderator between human resource development and alignment of higher education to addresses human resources challenge namely, organisational culture, organisational capabilities, and communication. The findings of the study believed will provide empirical evidence on how the alignment of higher education goals would mitigate human resource development challenges. Further, the importance of cointegration factors in the alignment of goals in higher education will be understood. At the practical level, the importance of strategic partnerships in higher education performance will also be understood.